Systemic steroid administration combined with intratympanic steroid injection in the treatment of a unilateral sudden hearing loss prognosis prediction model: A retrospective observational study - Yuan, Hao; Liu, Cheng-Cheng; Ma, Peng-Wei; Chen, Jia-Wei; Wang, Wei-Long; Gao, Wei; Lu, Pei-Heng; Ding, Xue-Rui; Lun, Yu-Qiang; Lu, Lian-Jun (Frontiers in Neurology, 2022)
Idiopathic sudden sensorineural hearing loss (ISSNHL) is an emergency ear disease that is referred to as a sensorineural hearing loss of at least 30 dB in three sequential frequencies and occurs over a period of less than 72 hours. Because of its etiology, pathogenesis, and prognostic factors, the current treatment methods are not ideal. Previous studies have developed prognostic models to predict hearing recovery from ISSNHL, but few studies have incorporated serum biochemical indicators into previous models. The aim of this study was to explore the factors influencing the ISSNHL prognosis of combination therapy (combined intratympanic and systemic use of steroids, CT), among the patient population data, the serum biochemical indicators before the treatment, and the clinical features of ISSNHL. The new prediction model was developed through these factors. From November 2015 to April 2022, 430 patients who underwent CT at the Department of Otorhinolaryngology Head and Neck Surgery, Tangdu Hospital, Air Force Medical University for ISSNHL, were reviewed retrospectively. We found significant differences in age (P=0.018), glucose (P=0.035), white blood cell (WBC) (P=0.021), vertigo (P=0.000) and type (P=0.000) with different therapeutic efficaciesy. Multivariate logistic regression analysis showed that age (OR=0.715, P=0.023), WBC (OR=0.527, P=0.01), platelet to lymphocyte ratio (PLR) (OR=0.995, P=0.038), vertigo (OR=0.48, P=0.004), course (time from onset to treatment) (OR=0.681, P=0.016) and type (OR=0.409, P=0.000) were independent risk factors for ISSNHL prognosis. Based on independent risk factors, a predictive model and nomogram were developed to predict hearing outcomes in ISSNHL patients. The area under the curve (AUC) value of the model developed in this study was 0.773 (95% CI =0.730-0.812), which has a certain predictive ability. The calibration curve indicated good consistency between the actual diagnosed therapeutic effectiveness and the predicted probability. The model and nomogram can predict the hearing prognosis of ISSNHL patients treated with CT and can provide help for medical staff to make the best clinical decision. This study has been registered with the registration number ChiCTR2200061379.